Study of an Atmospheric Refractivity Estimation from a Clutter Using Genetic Algorithm - Jang, Doyoung; Kim, Jongmann; Park, Yong Bae; Choo, Hosung (Applied Sciences (Switzerland), 2022)
Featured Application: This article is related to atmospheric refractivity estimation from clutter images using a genetic algorithm. In this paper, a method for estimating atmospheric refractivity from sea and land clutters is proposed. To estimate the atmospheric refractivity, clutter power spectrums based on an artificial tri-linear model are calculated using an Advanced Refractive Prediction System (AREPS) simulator. Then, the clutter power spectrums are again obtained based on the measured atmospheric refractivity data using the AREPS simulator. In actual operation, this spectrum from measured reflectivity can be replaced with real-time clutter spectrums collected from radars. A cost function for the genetic algorithm (GA) is then defined based on the difference between the two clutter power spectrums to predict the atmospheric refractivity using the artificial tri-linear model. The optimum variables of the tri-linear model are determined at a minimum cost in the GA process. The results demonstrate that atmospheric refractivity can be predicted using the proposed method from the clutter powers.
Keywords: clutter images; optimization algorithms; radar; radio propagation